Popularizing anti-semitism in early modern Spain and its empire (Review) - Valle, Enid (2020)
A book review of Popularizing anti-semitism in early modern Spain and its empire: Francisco de Torrejoncillo and the Centinela contra Judíos (1674) by François Soyer, reviewed by Enid Valle.